Analysis of Volleyball Top Service Skills in Extracurricular Students of Smpn 3 Batumandi: - Fauzi, M. Riki; Perdinanto; Anggara, Norma (Universitas PGRI Palembang, 2025)
Volleyball overhead serve skills are one of the important aspects in volleyball that require systematic evaluation to determine the level of skill of students. This study aims to determine the level of volleyball overhead serve skills of students of SMPN 3 Batumandi using quantitative descriptive methods and data collection techniques through volleyball overhead serve skills tests with 12 participants. The results showed that 4 people (33%) showed abilities in the good category with a score range of 21 to more than 41, 6 people (50%) were in the sufficient category with a score range of 13 to 40, and 2 people (17%) were included in the less category with a score range of 3 to 26. These results indicate that most students have overhead serve skills in the sufficient category. These results indicate that it is still necessary to improve volleyball overhead serve skills through a more structured and intensive training program, so it is recommended that coaches or schools can develop more effective training programs to improve volleyball overhead serve skills of students of SMPN 3 Batumandi.